2015
DOI: 10.2174/1570161113666150827125040
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Treatment of Patients with Homozygous Familial Hypercholesterolaemia: Information and Recommendations from a Middle East Advisory Panel

Abstract: We present clinical practice guidelines for the diagnosis and treatment of homozygous familial hypercholesterolaemia (HoFH) in the Middle East region. While guidelines are broadly applicable in Europe, in the Middle East we experience a range of confounding factors that complicate disease management to a point whereby the European guidance cannot be applied without significant modification. Specifically, for disease prevalence, the Middle East region has an established epidemic of diabetes and metabolic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 62 publications
0
41
1
Order By: Relevance
“…Historically, a patient was clinically diagnosed with HoFH, if he/she had untreated LDL-C > 13 mmol/L (500 mg/dL) or treated LDL-C > 8 mmol/L (300 mg/dL), and the presence of TXs before the age of 10 years, or the patient’s parents were diagnosed with HeFH 22 . However, the range of LDL-C levels reported in HoFH patients is broad and can overlap with ranges found in other types of FH 15,22 , which is another challenge for identification. Two cases of Iranian children with HoFH have reported severe septum and complex CHD outcomes 23,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, a patient was clinically diagnosed with HoFH, if he/she had untreated LDL-C > 13 mmol/L (500 mg/dL) or treated LDL-C > 8 mmol/L (300 mg/dL), and the presence of TXs before the age of 10 years, or the patient’s parents were diagnosed with HeFH 22 . However, the range of LDL-C levels reported in HoFH patients is broad and can overlap with ranges found in other types of FH 15,22 , which is another challenge for identification. Two cases of Iranian children with HoFH have reported severe septum and complex CHD outcomes 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, clinical practice guidelines for the diagnosis and treatment of HoFH in the Middle East region was published, which showed several factors such as consanguineous marriages, treatment accessibility and cascade screening limitations that were not found in Western countries 15 . Previous Iranian FH Genetic studies have used limited genetic screening methods based on PCR technology 16–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated LDL-C in FH is present from birth and there is evidence that the prognosis of both heterozygous and homozygous FH is improved with early treatment [4]. Detection of FH via clinical assessment alone can be particularly challenging in patients where LDL-C elevation is less marked [29] and the CVD risk levels of patients with FH may not accurately be predicted by the use of multivariate risk scoring (see Section 3) [4]. Therefore, genetic screening should be considered to identify common mutations causing FH in the region for new-borns with LDL-C elevation or clinical signs suggestive of FH.…”
Section: Genetic Testingmentioning
confidence: 99%
“…A systematic literature review identified 57 mutations in the Middle East and North Africa [30]; Table 1 summarises those reported in Middle Eastern countries. To date, the availability and uptake of genetic testing for FH in the Middle East has been limited [29].…”
Section: Genetic Testingmentioning
confidence: 99%
See 1 more Smart Citation